Strategic drivers of corporate capital structure - AZZA , Meryem; ACHIBANE , Mustapha (Revue Internationale des Sciences de Gestion, 2026)
This article examines the determinants of corporate capital structure by highlighting the complexity and diversity of factors influencing firms financing decisions. It shows that capital structure choices result from a strategic balance between financial constraints, growth prospects, risk considerations, and economic conditions. Firms adjust their use of debt and equity in response to their ability to generate cash flows, manage financial risk, and sustain long-term value creation. The analysis also emphasizes the role of taxation mechanisms, particularly non-debt tax shields, as an alternative to debt-related tax advantages. These mechanisms allow firms to optimize their tax burden while limiting excessive leverage and preserving financial flexibility. The findings suggest that capital structure decisions cannot be explained by a single theoretical framework, as firms adapt their financing strategies to changing market conditions and strategic objectives. Overall, the article concludes that effective capital structure management requires a flexible and context-dependent approach, enabling firms to balance risk and return, support sustainable growth, and strengthen their financial resilience in an increasingly uncertain economic environment.